2022
DOI: 10.1088/1361-665x/ac6919
|View full text |Cite
|
Sign up to set email alerts
|

Research on the vibration transmission characteristics of quasi-periodic impedance layered structure constructed by magnetorheological fluid

Abstract: In this work, the theoretical and experimental study on vibration transmission in quasi-periodic impedance layered structures built by magnetorheological (MR) fluid is conducted. Based on the MR effect of MR fluid, the quasi-periodic layered structures formed by low and high impedance layers following Fibonacci, Thue-Morse and multiperiodic sequences are constructed, respectively. These different quasi-periodic patterns can be flexibly obtained by controlling the arrangement style and magnetic field strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It can be seen that the TMF can change the nature of the mechanical impedance of the gradient material by changing the interaction between the particle layers inside the MRF, which suggests that the mechanical impedance of the gradient material can be adjusted by adjusting the parameters of the TMF, to change its vibration transfer characteristics. However, the mechanical impedance cannot visually express the attenuation performance of gradient materials against external excitation, so it is necessary to calculate further the vibration level difference based on mechanical impedance and characterize the vibration transmission properties of gradient materials under the action of the TMF through the vibration level difference [12][13][14].…”
Section: The Variation Law Of Mechanical Impedance Of Magnetorheologi...mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that the TMF can change the nature of the mechanical impedance of the gradient material by changing the interaction between the particle layers inside the MRF, which suggests that the mechanical impedance of the gradient material can be adjusted by adjusting the parameters of the TMF, to change its vibration transfer characteristics. However, the mechanical impedance cannot visually express the attenuation performance of gradient materials against external excitation, so it is necessary to calculate further the vibration level difference based on mechanical impedance and characterize the vibration transmission properties of gradient materials under the action of the TMF through the vibration level difference [12][13][14].…”
Section: The Variation Law Of Mechanical Impedance Of Magnetorheologi...mentioning
confidence: 99%
“…At the same time, the vibration level difference can well reflect the vibration pression effect of adjustable gradient materials. Therefore, this paper adopts the vibration level difference as the evaluation index of vibration transfer characteristics of adjustable gradient materials [12][13][14].…”
Section: Solution and Analysis Of Vibration Transmission Characterist...mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the energy storage modulus of MRF increases linearly with frequency. Si et al [8] constructed a quasi-periodic structure using MRF by changing the thickness and arrangement of the MRF's high and low impedance layers and investigated its vibration transfer characteristics, and found that the quasi-periodic structure has better vibration attenuation in a specific frequency range. Liu et al [9] and Zhao et al [7,10] built a modulable impedance structure based on the rheological properties of the MRF, equated the MRF to a saturated porous medium using Biot theory and equivalent medium theory, established the transmission model of elastic waves in the modulable impedance structure and solved it numerically.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the components of MRF can well explain the shear and chain formation mechanism by analyzing them. However, for the vibration transfer properties of MRF, the influence of the composition parameters has not been investigated from a microscopic perspective [7,8,10,19,20].…”
Section: Introductionmentioning
confidence: 99%